Some observations on borrowings in the Russian dialect on the Kola Peninsula - Pineda, David (Universitetet i Tromsø, 2004)
The present article gives an overview of the borrowed vocabulary of the Russian dialect of the Kola peninsula, which mostly comes from Finno-Ugric languages. Some remarks are made as to the phonetical and morphological adaptations to Russian, the etymology and the distribution of the loanwords over the different semantic fields. Not surprisingly, the terminology on reindeer husbandry is dominated by loans from Sámi languages. Some names for fishes are also Sámi, but fishing terminology is almost exclusively borrowed from Baltic-Finnic. Other source languages include Samoyedic (clothing), Norwegian and Dutch (ship types).